Roads, rails, and checkpoints: Assessing the permeability of nation-state borders worldwide. (April 2023) - Deutschmann, Emanuel; Gabrielli, Lorenzo; Recchi, Ettore
Highlights: A novel border permeability dataset is created, covering 312 land borders globally. More (and better) cross-border transport infrastructure and fewer checkpoints lead to higher border permeability. Europe and Western and Eastern Africa have the most permeable and the Americas the least permeable borders worldwide. Economic development is by far the most relevant explanatory factor of border permeability. Borders of rich and poor countries are highly permeable, but those of moderately prosperous countries are harder to cross. Abstract: The permeability of nation-state borders determines the flow of people and commodities between countries and therefore greatly influences many aspects of human development from trade and economic inequality to migration and the ethnic composition of societies worldwide. While past research on the topic has focused on border fortification (walls, fences, etc.) or the legal dimension of border controls, we take a different approach by arguing that transport infrastructure (paths, roads, railroads, ferries) together with political checkpoints can be used as valuable indicators for the permeability of borders worldwide. More and better transport infrastructure increases permeability, whereas checkpoints create the political capacity for reducing entries. Using automatized computational methods combined with extensive manual checks, we parse data from OpenStreetMap and the World Food Programme to detect cross-border transport infrastructure and checkpoints. Based on this information, we define an index of border permeability for 312 land borders globally. Subsequent analyses show that regardless of the degree of closure enforcement at checkpoints, Europe and Africa have the most, and the Americas the least, permeable borders worldwide. Regression models reveal that border permeability is higher in densely populated areas and that economic development, by far the most relevant explanatory factor, has a curvilinear relationship with border permeability: Borders of very rich and very poor countries are highly permeable, whereas those of moderately prosperous nation-states are significantly harder to cross. Implications of this remarkably clear pattern are discussed.